2021
DOI: 10.1002/sce.21693
|View full text |Cite
|
Sign up to set email alerts
|

Science teachers’ and students’ metavisualization in scientific modeling

Abstract: This study investigated eight experienced science teachers’ and eight senior high school students’ metavisualization when they drew models to represent their concepts of carbon cycling. Qualitative data collection techniques including think‐aloud tasks and follow‐up retrospective interviews were employed. The purposes of the study included: (1) to propose a framework differentiating performance levels leading to metavisual competence; and (2) to identify students’ metavisualization difficulties by comparing ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Representation can thus be seen as a means of communicating ideas of science or mathematics (Ngin, 2018). The scope of multiple representations takes the form of models, spaces, symbols, and visuals to achieve the purpose of science learning epistemically (Chang, 2021).…”
Section: Multiple Representation Approach Learning Conceptmentioning
confidence: 99%
“…Representation can thus be seen as a means of communicating ideas of science or mathematics (Ngin, 2018). The scope of multiple representations takes the form of models, spaces, symbols, and visuals to achieve the purpose of science learning epistemically (Chang, 2021).…”
Section: Multiple Representation Approach Learning Conceptmentioning
confidence: 99%
“…Previous research has indicated that providing students with visual representations can facilitate students' SM (Barak & Hussein-Farraj, 2013;Chang, 2022;Chittleborough & Treagust, 2008). The computerbased interactive tasks can present visual representations of phenomena and provide timely feedback to students' performance, which can create a supportive SM environment for students.…”
Section: / 13mentioning
confidence: 99%